Outcomes in chronic lymphocytic leukemia patients on novel agents in the US Veterans Health Administration System. Issue 7 (7th June 2021) - Frei, Christopher R.; Le, Hannah; McHugh, Daniel; Ryan, Kellie; Jones, Xavier; Galley, Samantha; Franklin, Kathleen; Baus, Courtney J.; Tavera, Juan; Janania-Martinez, Michelle; Gregorio, David; Ananth, Snegha; et al.
Abstract: The US veteran population has a high proportion of chronic lymphocytic leukemia (CLL) risk factors. Using the Veterans Health Administration (VHA) population, we conducted a retrospective chart review of 1205 CLL patients who initiated treatment with a novel oral agent. For 1L ibrutinib, 33% ( n = 107) discontinued therapy during the study, of which 64% discontinued due to adverse events (AEs). For relapsed/refractory (R/R) ibrutinib, 35% ( n = 262) discontinued therapy, of which 63% discontinued due to AEs. For R/R venetoclax, 31% ( n = 27) discontinued therapy, of which 41% were due to AEs. For idelalisib, 84% ( n = 41) discontinued therapy, of which 54% were due to AEs. This real-world study suggests that AEs play an important role in dose reductions and discontinuations; however, physician inexperience in using these drugs when they were first introduced could be part of what is leading to these negative outcomes.